2019
DOI: 10.2147/cia.s214935
|View full text |Cite
|
Sign up to set email alerts
|

<p>A simple method to minimize leg length discrepancy in hip hemiarthroplasty</p>

Abstract: PurposeWe developed a simple method to minimize leg length discrepancy (LLD) during hip arthroplasty. The purpose of this study is to evaluate the accuracy of the method.Patients and methodsA total of 47 patients who suffered from unilateral femoral neck fracture and underwent hip hemiarthroplasty between 2015 and 2018 were enrolled in this study. We measured the diameter of the contralateral femoral head (D) and the distance (L) between the center of the femoral head and the top of lesser trochanter in the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The reliability of the anatomical markers for the bilateral leg length discrepancy after hip arthroplasty for femoral neck fractures was compared. Wang et al ( 26 ) determined the osteotomy line and the depth of prosthesis implantation by measuring the diameter of the contralateral femoral head and the distance from the center of the femoral head to the apex of the lesser trochanter. A satisfactory bilateral lower extremity length was obtained after HA in 47 elderly patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reliability of the anatomical markers for the bilateral leg length discrepancy after hip arthroplasty for femoral neck fractures was compared. Wang et al ( 26 ) determined the osteotomy line and the depth of prosthesis implantation by measuring the diameter of the contralateral femoral head and the distance from the center of the femoral head to the apex of the lesser trochanter. A satisfactory bilateral lower extremity length was obtained after HA in 47 elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…It was combined with preoperative AIHIP planning ball-joint model number fitting for reduction to confirm the model number of the femoral head prosthesis. Wang et al ( 26 ) suggested that accurate osteotomy and measurement of the femoral side can reduce the bilateral leg length discrepancy after THA. In this study, the femoral “shoulder” was identified as the anatomical marker ( Figure 2B ), and the proximal end of the template was placed at the “shoulder” of the marked femur ( Figure 2D ), according to the osteotomy template, the osteotomy line was marked on the femoral neck, and then the osteotomy was performed accurately.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study (13), we measured the contralateral side femoral head diameter (non-fracture side) and the distance from the femoral head center to the lesser trochanter in antero-posterior pelvic X-ray film before hip hemiarthroplasty for a patient with femoral neck fracture, and calculated the ratio of this distance to the diameter. During surgery, after measuring the femoral head diameter (fracture side) with a vernier caliper.…”
Section: Discussionmentioning
confidence: 99%
“…X-ray cannot accurately show the thickness of cartilage. Different from the best fit circle method (12), and same as our previous research (13), the circle measuring the femoral head diameter was drawn through the midline of the gap between the superior surface of the femoral head and the acetabulum. Previous study showed that the femoral head cartilage thickness was 1.76±0.30 mm and the acetabular cartilage thickness was 1.59±0.31 mm in this area, with an average difference of 0.17 mm between them (20).…”
Section: Discussionmentioning
confidence: 99%
“…With the progressive aging of the population, the incidence of hip fractures is increasing worldwide [ 1 ]. Hip arthroplasty is an effective therapy for treating femoral neck fractures, which can rapidly reconstruct hip function and avoid a series of complications such as infection and thrombosis caused by long-term bed rest, and can effectively reduce the morbidity and mortality rate while improving patients' quality of life [ 2 ].…”
Section: Introductionmentioning
confidence: 99%